Measurements of atmospheric pollutants in Alaska (abstract) - Ohta, Sachio; Murao, Naoto; Hayashi, Kentaro (National Institute of Polar Research, 1993)
P(論文) Atmospheric aerosols and gaseous constituents were measured from September 1990 through July 1991 at the top of Ester Dome, 10km west of Fairbanks, Alaska. In September 1990 through May 1991 atmospheric concentrations of total particulate matter less than 2 departmental bulletin paper